Metabolic oscillations on the circadian time scale in Drosophila cells lacking clock genes. Issue 8 (6th August 2018) - Rey, Guillaume; Milev, Nikolay B; Valekunja, Utham K; Ch, Ratnasekhar; Ray, Sandipan; Silva Dos Santos, Mariana; Nagy, Andras D; Antrobus, Robin; MacRae, James I; Reddy, Akhilesh B
Abstract: Circadian rhythms are cell‐autonomous biological oscillations with a period of about 24 h. Current models propose that transcriptional feedback loops are the primary mechanism for the generation of circadian oscillations. Within this framework, Drosophila S2 cells are regarded as "non‐rhythmic" cells, as they do not express several canonical circadian components. Using an unbiased multi‐omics approach, we made the surprising discovery that Drosophila S2 cells do in fact display widespread daily rhythms. Transcriptomics and proteomics analyses revealed that hundreds of genes and their products, and in particular metabolic enzymes, are rhythmically expressed in a 24‐h cycle. Metabolomics analyses extended these findings and demonstrate that central carbon metabolism and amino acid metabolism are core metabolic pathways driven by protein rhythms. We thus demonstrate that 24‐h metabolic oscillations, coupled to gene and protein cycles, take place in nucleated cells without the contribution of any known circadian regulators. These results therefore suggest a reconsideration of existing models of the clockwork in Drosophila and other eukaryotic systems. Synopsis: Integrative transcriptomics and proteomics analyses show that Drosophila S2 cells show daily oscillations in gene expression and metabolism, despite the fact that they do not express a functional circadian transcriptional clockwork. Drosophila S2 cells do not express several canonical circadian components. Multi‐omics analyses show that Drosophila S2 cells display widespread daily rhythms at the level of transcripts, protein and metabolites. Integrative analyses indicate a strong coupling between metabolic and gene expression cycles. Abstract : Integrative transcriptomics and proteomics analyses show that Drosophila S2 cells show daily oscillations in gene expression and metabolism, despite the fact that they do not express a functional circadian transcriptional clockwork.